Penerapan SAK-ETAP Sebagai Upaya Peningkatan Kualitas Laporan Keuangan UKM - Sungkono Sungkono (EBBANK, 2010)
The objective of financial statements are to provide information about the financial position, performance and change in financial position of an enterprise that is useful in making business  decisions. The facts have shown that Small and Medium Enterprises (SME’s) encounter financial reporting difficulties due to a major internal weakness in their business. One of their problems is entrepreneurs of SME’s may fail to recognize the importance of financial statement and accounting information that could be utilitized in decision making. Consequently, quality of financial statement that they prepared are not sufficient for many purposes. SAK-ETAP is a new product of IAI as financial accounting standard for SME’s. This product is prepared more simple than general financial accounting standard (SAK) , so Entrepreneurs of SME’s can apply fluently in accounting processes, and so far financial statements is prepared more useful for business decision making